Roles of Interaction between CCN2 and Rab14 in Aggrecan Production by Chondrocytes - Hoshijima, Mitsuhiro (Int J Mol Sci, 2020)
To identify proteins that cooperate with cellular communication network factor 2 (CCN2), we carried out GAL4-based yeast two-hybrid screening using a cDNA library derived from the chondrocytic cell line HCS-2/8. Rab14 GTPase (Rab14) polypeptide was selected as a CCN2-interactive protein. The interaction between CCN2 and Rab14 in HCS-2/8 cells was confirmed using the in situ proximity ligation assay. We also found that CCN2 interacted with Rab14 through its IGFBP-like domain among the four domains in CCN2 protein. To detect the colocalization between CCN2 and Rab14 in the cells in detail, CCN2, wild-type Rab14 (Rab14WT), a constitutive active form (Rab14CA), and a dominant negative form (Rab14DN) of Rab14 were overexpressed in monkey kidney-tissue derived COS7 cells. Ectopically overexpressed Rab14 showed a diffuse cytosolic distribution in COS7 cells; however, when Rab14WT was overexpressed with CCN2, the Rab14WT distribution changed to dots that were evenly distributed within the cytosol, and both Rab14 and CCN2 showed clear colocalization. When Rab14CA was overexpressed with CCN2, Rab14CA and CCN2 also showed good localization as dots, but their distribution was more widespread within cytosol. The coexpression of Rab14DN and CCN2 also showed a dotted codistribution but was more concentrated in the perinuclear area. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) analysis revealed that the reduction in RAB14 or CCN2 mRNA by their respective siRNA significantly enhanced the expression of ER stress markers, BIP and CHOP mRNA in HCS-2/8 chondrocytic cells, suggesting that ER and Golgi stress were induced by the inhibition of membrane vesicle transfer via the suppression of CCN2 or Rab14. Moreover, to study the effect of the interaction between CCN2 and its interactive protein Rab14 on proteoglycan synthesis, we overexpressed Rab14WT or Rab14CA or Rab14DN in HCS-2/8 cells and found that the overexpression of Rab14DN decreased the extracellular proteoglycan accumulation more than the overexpression of Rab14WT/CA did in the chondrocytic cells. These results suggest that intracellular CCN2 is associated with Rab14 on proteoglycan-containing vesicles during their transport from the Golgi apparatus to endosomes in chondrocytes and that this association may play a role in proteoglycan secretion by chondrocytes.